Dispersion in the Presence of Acetic Acid or Ammonia Confers Gliadin‐Like Characteristics to the Glutenin in Wheat Gluten. Issue 2 (14th January 2015) - Murakami, Tetsuya; Kitabatake, Naofumi; Tani, Fumito
Abstract Spray‐dried gluten has unique properties and is commercially available in the food industry worldwide. In this study, we examined the viscoelastic properties of gluten powder prepared by dispersion in the presence of acetic acid or an ammonia solvent and then followed by lyophilization instead of a spray drying. Mixograph measurements showed that the acid‐ and ammonia‐treated gluten powders had marked decreases in the time to peak dough resistance when compared with the control gluten powder. The integrals of the dough resistance and bandwidth for 3 min after peak dough resistance decreased in both treated gluten powders. Similar phenomena were observed when gliadin was supplemented to gluten powders. Basic and acidic conditions were applied to the acid‐ and ammonia‐treated gluten powders, respectively, and the viscoelastic behaviors were found to depend on the pH in the gluten dispersion just before lyophilization. These behaviors suggest that gluten may assume a reversible change in viscoelasticity by a fluctuation in pH during gluten dispersion. SDS‐PAGE showed that the extractable proteins substantially increased in some polymeric glutenins including the low molecular weight‐glutenin subunit (LMW‐GS) when the ammonia‐treated gluten powder was extracted with 70% ethanol. In contrast, the extractable proteins markedly increased in many polymeric glutenins including the high molecular weight‐glutenin subunit and/or the LMW‐GS when the acid‐treated gluten powder was extracted with 70% ethanol. It thus follows that the extractability of polymeric glutenin to ethanol increases similarly to gliadin when gluten is exposed to an acidic or a basic pH condition; therefore, glutenin adopts gliadin‐like characteristics.